Who speaks? : renegotiating sovereign and metaphysical discourses in politics and law. - Bertolino, Elisabetta R. (Soft Power, 2016)
The article deals with the theme of the subject in politics and law, which is essentially also the theme of who speaks. A focus on the voice is regarded here as paramount.